When Teachers Were Farmers: Teachers’ Allotted Farms and the Funding of Mass Schooling, 1838–1900 - Westberg, Johannes (Nordic Journal of Educational History, 2015)
What were teachers’ allotted farms, and what were they for? This study aims to answer these questions by examining these farms in nineteenth century Sweden, and their role in the expansion of the elementary school system in 1838–1900. Focusing on the allotted farms of the Sundsvall region, this article analyses how these farms provided teachers with fields and meadows, as well as outhouses such as cowsheds, bakehouses and cellars. This article argues that these farms made schooling more affordable for the school districts, primarily in the first two decades after the Elementary School Act of 1842. Allotted farms were often inexpensive to acquire and maintain, not least owing to the agricultural and maintenance work that the teachers carried out, and yielded an annual return that reduced the taxation needed to operate the school districts. This, in turn, facilitated the expansion of schooling.